Association of inappropriate left ventricular mass with systolic and diastolic dysfunction: The HyperGEN study - DE SIMONE, Giovanni; KITZMAN, Dalane W; PALMIERI, Vittorio; LIU, Jennifer E; OBERMAN, Albert; HOPKINS, Paul N; BELLA, Jonathan N; RAO, D. C; ARNETT, Donna K; DEVEREUX, Richard B (American journal of hypertension, 2004)
Left ventricular mass (LVM) exceeding values appropriate for individual workload is associated with concentric LV geometry and systolic dysfunction at both the midwall and chamber levels, even independently of clearcut LV hypertrophy, and is a marker of adverse prognosis. No information is available on whether inappropriate LVM is associated with alterations of LV diastolic properties in unselected population-based studies. We examined 1513 hypertensive participants from the HyperGEN population who were without prevalent cardiovascular disease. The LVM prediction from stroke work (systolic blood pressure x Doppler stroke volume), sex, and height (in meters2.7) was derived in 210 nonobese, normal individuals. Observed/predicted LVM >133% defined inappropriate LVM. Participants with inappropriate LVM (229 subjects [15%]) exhibited higher LV dimensions and relative wall thickness, lower ejection fraction, midwall shortening and cardiac output, and prolonged isovolumic relaxation time (IVRT; P < or = .001). Other diastolic abnormalities were not associated with inappropriate LVM. After accounting for demographic and hemodynamic confounders, IVRT was directly related to excess LVM, whereas deceleration time of E velocity was negatively related to excess LVM. Nonechocardiographic correlates of prolonged relaxation included aging, African American ethnicity, male gender, and diabetes. The LVM exceeding the compensatory needs for workload is associated with delayed LV relaxation as well as mild midwall and chamber systolic dysfunction, independently of demographic, clinical, and hemodynamic confounders. Inappropriately high LVM also correlates with features of increased myocardial stiffness, coexisting with evidence of prolonged LV relaxation.